STRATEGI PEMBELAJARAN PAI PADA METODE BELAJAR, MENGHAFAL DAN MENTERJEMAH ALQUR’AN - Sudianto Sudianto (Cross-border, 2021)
Islamic religious education learning strategies vary, both from methods, models, techniques and learning approaches, but in particular there are differences between the subjects taught to students and learning strategies on learning methods, memorizing and translating the Koran. In fact, to implement this strategy, a teacher and students need to know about etiquette in reading the Koran. The study of this research is qualitative by using a literature review where the results of the study found that; First, the learning strategy in each subject is the same, but it is different from learning, memorizing and translating the Qur'an, where every student and teacher needs to apply adab in learning the Qur'an. Second, every subject has intrinsic elements, both internal and external, as well as learning strategies for the Qur'an.